STRATEGI PERCEPATAN PERGANTIAN ADMINISTRASI KEPENDUDUKAN PASCA PEMEKARAN KECAMATAN DI KOTA PEKANBARU - Sari, Riowa Melina; Mashur, Dadang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Pekanbaru City experienced expansion from 12 sub-districts to 15 sub-districts. This has an impact on the people who live in the area resulting from the sub-district expansion. There is a special strategy using SWOT Analysis in the change of population administration after the expansion of sub-districts in Pekanbaru City where the strategy will be used by human resources who handle it in the Pekanbaru City Population and Civil Registration Office agency. This research uses qualitative research methods that are descriptive in nature. The purpose of this research is to find out the efforts that have been made by the Pekanbaru City government in the replacement of population administration after the expansion of sub-districts in Pekanbaru City, and to find out the strategy for accelerating the replacement of population administration after the expansion of sub-districts in Pekanbaru City using SWOT analysis. Based on the results of the SWOT analysis, the strategy recommendation given is an Aggressive Strategy. The results of the study indicate that the replacement of population administration after sub-district expansion through the Population and Civil Registration Office of Pekanbaru City has not run optimally so that the resulting strategy can increase public awareness about the replacement of population administration after sub-district expansion in Pekanbaru City. The existence of a program from the Population and Civil Registration Office of Pekanbaru City in the form of Sipenduduk online services should be further socialized to RT and RW by providing training in using these online services. Keywords: Population Administration, SWOT Analysis, Strategy